The Use of EGRA Technique to Teach Simple Past Tense - Kalebo, Lut Gardania Pama; Regina, Regina; Wardah, Wardah (Universitas Tanjungpura, 2024)
The purpose of this study was to determine whether or not the EGRA (Experience, Generalization, Reinforcement, and Application) technique had a significant effect on how the eighth-grade students at SMPN 1 Sekayam were taught the simple past tense. The investigation was conducted as a pre-experimental design. 30 students from VIII A were selected as the sample for this study using cluster sampling. The outcome of the data analysis showed that the value of the students' pre - test and post-test varied. The pretest's mean score was 32.00, whereas the posttest's mean score was 84.00. It indicates that the pupils understood the simple past tense well after using the EGRA method to teach them. Furthermore, the result of the paired-sample test t-test showed .000 which was 0.05. The results showed that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The findings showed that the EGRA Technique significantly affects the teaching of simple past tense.